1964
DOI: 10.1002/pol.1964.100020305
|View full text |Cite
|
Sign up to set email alerts
|

Photosensitized polymerization of acrylic monomers. II. Kinetics of polymerization in the presence of oxygen

Abstract: The kinetics of the photopolymerization of acrylamide and methacrylic acid in aqueous and semi‐organic solutions have been examined; the initiating redox system used in the presence of oxygen were eosin‐thiourea, eosin‐1‐ascorbic acid, or in some cases riboflavine. The rates of photopolymerization were determined by measuring the thermal rise of the reaction cell using a thermistor technique. In aqueous and in semi‐organic solutions, the rate is proportional to the square of the monomer concentration in both c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

1968
1968
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…Recently two groups of workers 1 -2 d have used these reducing agents with H202 as the oxidant for initiation in the aqueous polymerization of acrylonitrile and suggested a tentative reaction mechanism on the basis of their kinetic studies. DELZENNE et al 3), while conducting a dye (Eosin)-sensitized aqueous photopolymerization of acrylamide in an oxygen atmosphere, concluded that the initiating redox system actually consists of thiourea and H202. The incorporation of an amino-bearing end group in the resultant polymer by redox systems containing thiourea was confirmed by MUKHERJEE et al 4) utilizing dye-partition technique.…”
Section: Introductionmentioning
confidence: 99%
“…Recently two groups of workers 1 -2 d have used these reducing agents with H202 as the oxidant for initiation in the aqueous polymerization of acrylonitrile and suggested a tentative reaction mechanism on the basis of their kinetic studies. DELZENNE et al 3), while conducting a dye (Eosin)-sensitized aqueous photopolymerization of acrylamide in an oxygen atmosphere, concluded that the initiating redox system actually consists of thiourea and H202. The incorporation of an amino-bearing end group in the resultant polymer by redox systems containing thiourea was confirmed by MUKHERJEE et al 4) utilizing dye-partition technique.…”
Section: Introductionmentioning
confidence: 99%
“…For the purpose of this study, Eosin has been selected as the light‐absorbing component, because from among xanthene dyes, Eosin was used most often for photoinitiation of free radical polymerization of monomers. For aqueous solutions of monomers, such as acrylamide or metal acrylates, sodium salts of Eosin (e.g., Eosin Y) were used, which were well soluble in water 19–24. However, most of photocurable monomers used in practice are not soluble in water, while Eosin salts are not soluble in nonpolar media.…”
Section: Resultsmentioning
confidence: 99%
“…Various compounds, such as amines (e.g., aliphatic amines,25–36 aromatic amines,25, 34, 37 amino‐monomers,38–42 amino‐polymers43), halogenated compounds,44–46 oxime esters,47, 48 iodonium cations,49–54 and other oxidizing or reducing agents,23, 24, 41, 55–61 have been reported in literature as effective coinitiators for Eosin/coinitiator systems. Eosin/amine systems were used most often, either alone or in combination with other coinitiators or UV photoinitiators 29, 42, 62, 63.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, there is a trend to use safe photoinitiators. For example, riboflavin (vitamin B2), is a water‐soluble natural dye [13] which has been used as early as 1964 to photopolymerize an aqueous acrylamide under visible light [14] . Subsequently, resins for photocurable films were formulated based on riboflavin and co‐initiators such as amines, [15] amino acids with L‐arginine [16] and tyrosine, [17] thiols with dithiothreitol [18] or proteins [19] .…”
Section: Introductionmentioning
confidence: 99%